Sejarah Tafsir Indonesia Abad ke XX - Muhammad Amin (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2021)
Indonesian interpretation of the Koran has developed since the sixteenth century in Aceh. However, the massive development of this interpretation only occurred in the twentieth century. In this article, the author describes the history of the study of interpretation in Indonesia in the twentieth century along with its features, objects, and characteristics. The first period of the twentieth century started from 1900s to the 1960s with the object of interpretation in the form of selected letters such as Surah Yasin and al-Fatihah as well as selected chapters such as 30th chapter. The second period between the 1970s and 1980s began to show a special pattern in interpretation of the Koran. This particular pattern has not been seen in the previous period. The pattern that emerged in this era was dominated by the study of Islamic jurisprudence or interpretation of legal verses. The third period, which began in the 1990s, was the culmination of the development of interpretation with the emergence of commentators who studied the Koran in relation to contemporary issues such as feminism. Among the characteristics of the twentieth century interpretation is the emergence of several interpretations written collectively. In addition, there were also several commentators who had non-Quranic academic background such as economics, social, and literature.